2021
DOI: 10.1016/j.psj.2021.101024
|View full text |Cite
|
Sign up to set email alerts
|

Effects and interaction of dietary calcium and nonphytate phosphorus for slow-growing yellow-feathered broilers between 56 and 84 d of age

Abstract: This experiment investigated the effect and interaction of dietary calcium ( Ca ) and nonphytate phosphorus ( NPP ) on growth performance, tibial characteristics, carcass traits, and meat quality for slow-growing yellow-feathered broilers during 56 to 84 d of age. A 3 × 3 factorial arrangement was used, and 720 56-day-old broilers were randomly divided into 9 groups and fed with diets containing different levels of Ca (0.70, 0.80, 0.90%) and NPP (0.30, 0.35, 0.40%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…As the most abundant minerals in the body, provision of appropriate amounts of dietary Ca and P is critical for poultry production. In addition to their accretion in bone, they are essential for biological processes such as intracellular signaling, and muscle contractions [ 1 , 10 ]. Excessive dietary Ca and P, however, have a harmful impact on growth of broilers [ 6 , 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…As the most abundant minerals in the body, provision of appropriate amounts of dietary Ca and P is critical for poultry production. In addition to their accretion in bone, they are essential for biological processes such as intracellular signaling, and muscle contractions [ 1 , 10 ]. Excessive dietary Ca and P, however, have a harmful impact on growth of broilers [ 6 , 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, our previous study on broilers aged 56 to 84 d also showed that dietary Ca level significantly affected shear force and dietary NPP level affected drip loss of breast muscle. The change of meat quality in the current research might be related to oxidative stress because poor meat quality of broilers is commonly seen along with oxidative damage, and NPP could reduce lipid and protein oxidation [ 10 ]. Under the present experimental conditions, for yellow-feathered broilers at finisher phase, dietary level of 0.75% Ca and 0.25% NPP achieved the best meat quality.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations